Case report of isolated lesser trochanter avulsion fracture - Asok, Anand; Jose, Jijo (International Journal of Research in Orthopaedics, 2025)
An isolated lesser trochanter avulsion fracture is a rare injury. It is of two types, true fracture which occurs only in adults or as epiphyseal separation which are found in adolescent population. It is caused by a sudden forceful eccentric contraction of the iliopsoas in an attempt to accelerate or decelerate the body. In this case report, 15 year old male football player presented with acute onset of pain while playing football, associated with difficulty in walking. On X ray, it was lesser trochanter avulsion fracture which was fixed with cortical screw with washer+ fibre wire+5 mm suture anchor. the outcome was good. The patient reverted to his obvious activities with normal range of movement. The minimal invasive surgical management have better outcome with faster healing, early mobilization, good range of hip movement.